Análisis de las cuentas por cobrar en el área comercial de TRANSVIAL EP 2022. - Bravo Loor, Franklin Francisco (2022)
The investigation analyzes the level of past due portfolio of the Municipal Public Enterprise Transport Terminal, Traffic Safety of Babahoyo, TRANSVIAL E.P., which makes evidence of unfavorable level for the administration interests, and that have not accomplished present control norms. It was set as objective to determine the causes that generates a high level of past due portfolio in the commercial area of TRANSVIAL E.P. 2022, in order to propose actions to solve them. It was necessary to carried out a documental analysis to get bibliographic data about processes, control, past due portfolio, as well as the analysis of Enterprise documents about the situation of the past due portfolio; it was also needed to executed an interview to the manager to know past and present actions to solve the problem. Finally, some potential causes were determined and also suggested some immediate actions.